Influence of the depreciation method on the wood transport cost - Sampaio,Iara Silva (2021)
ABSTRACT Wood transport, predominantly made by road in Brazil, represents one of the most costly segments of this sector. Depreciation, one of the fixed costs in forestry production, is included in the use and replacement of machines. Their depreciation is calculated by different methods and the best ones should be used to improve costs in wood industry. The objective of this study was to evaluate the influence of four depreciation methods on the cost of forest road transportation. The depreciation methods used were: Caires, Cole, Exponential and Linear. The depreciation and transportation costs were determined using the freight cost simulation spreadsheet for the Road Transportation of Loads, developed by the Agência Nacional de Transportes Terrestres (ANTT). The monthly depreciation of the truck was R$ 1,630.25, R$ 2,276.64, R$ 2,400.96 and R$ 2,422.40 with the Caires, Exponential, Linear and Cole methods, respectively. The lowest transport cost was R$ 13.71 with the Caires method, followed by R$ 13.72, R$ 16.72 and R$ 16.92 from the Linear, Cole and Exponential methods, respectively. The lower values of depreciation and transport cost per ton obtained by the Caires method are due to this method considering factors other than the current age and the useful life of the machine and adjusting the model and the coefficients of use for specific situations. This portrays the situations found in the field, generating costs closer to the real ones. The best estimation of the depreciation and wood transport cost was obtained with the Caires method in all the studied situations, evidencing the need to consider maintenance and labor factors in its calculation. The adoption of this method also represents a great saving of financial resources in the long term.